Surveillance of the Efficacy of Artemisinin–Piperaquine in the Treatment of Uncomplicated Plasmodium falciparum Malaria Among Children Under 5 Years of Age in Est-Mono District, Togo, in 2017 - Wang, Qi; Zhang, Zhenyan; Yu, Weisheng; Lu, Chenguang; Li, Guoming; Pan, Ziyi; Zhang, Hongying; Wu, Wanting; Oubou, Tinah Atcha; Yuan, Yueming; Guo, Jiawen; Liang, Yuan; et al. (Frontiers in Pharmacology, 2020)
Background Malaria is a major public health concern in Togo. The Est-Mono district of Togo has a population of 150,000. Accordingly, the Guangzhou University of Chinese Medicine, China and the Ministry of Health and Social Security, Togo launched a nationwide Mass Drug Administration Project with artemisinin-piperaquine(AP) in Est-Mono. Before launching this project, the sensitivity test of AP was conducted in a general clinic in Elawagnon, Togo. Methods Children aged 6–59 months with uncomplicated falciparum malaria were enrolled in this study. The selected patients were treated with a combination regime of artemisinin–piperaquine. The patients were followed up for 28 days, during which signs of the following were observed for: the duration for fever clearance, parasitemia density, gametophyte generation, cure rate, hemoglobin level, and merozoite surface protein-2 (msp-2) polymorphism. The primary end point was a 28-day cure rate and polymerase chain reaction (PCR)-corrected reinfection and recrudescence. This research followed the standardized World Health Organization (WHO) protocol for the assessment of the efficacy of anti-malarial drugs. Results A total of 91 children with uncomplicated falciparum malaria were enrolled in this study. Adequate clinical and parasitological response (ACPR) before and after PCR-correction were 66 (73%) and 90 (99%), respectively. The average hemoglobin level in the patient increased by 0.05 g/dL per day (p < 0.0001) after the treatment. The gametophyte generation did not decline at the beginning of the treatment; however, after 14 days, it declined (day 21: p < 0.05; day 28: p < 0.01). In the msp-2 polymorphism study of 24 children treated for parasite infection, 1 case of msp-2 with 3D7 haplotype and FC27 haplotype was noted, indicating its recrudescence, with a frequency of 4%. The remaining 23 cases could have been of reinfection, with a frequency of 96%. No serious adverse reactions occurred, and AP was well-tolerated by all patients. Conclusion Artemisinin–piperaquine was found to be an effective combination for treating uncomplicated falciparum malaria in children aged <5 years in Togo, and the drugs were well-tolerated. In Togo, Plasmodium falciparum remains sensitive to artemisinin–piperaquine, necessitating its trial in this region.